The Relations of the Muslims of Turkey & India: A Study of the Efforts of Zafar Ali Khan - Zahid Munir Amir (بازیافت, 2019)
Maulana Zafar Ali Khan( 1873---1956) was an epoch-making personality who rendered his services in the fields of journalism, poetry and translations. Besides his literary endeavours, he played a pivotal role in the Khilafat Movement. He contributed in this historical movement as a mainstream leader and collected a sum of money to help the Turks, during their trying times. To present this amount and other gifts from Indian Muslims, he travelled to Turkey and presented these gestures of love to the Sultan of that time. In this article, details of his journey, along with his  poetical works regarding the Turks are being produced. Some historical documents regarding these efforts have been discovered and presented in this article, for the first time.